Un modelo de rutas para la recolección de residuos sólidos domiciliarios: Un caso de estudio; Case study for household solid waste collection - Lina Clemencia Bustamante Gutiérrez; Ángela María Alzate Álvarez; Paola Marcela Alzate Montoya (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– The integrated management of solid waste at the household level involves adequate collection logistics for recovery by waste collectors. The objective of this study was to optimize the route for access to waste at strategic points in the city of Manizales (Colombia), in addition to analyzing the qualitative characteristics related to a process of sensitization of the executing personnel. The integration of the numerical inputs and study variables was carried out through the application of the Shortest Route optimization algorithm, while the SWOT matrix was implemented to analyze the operational satisfaction conditions. The results generated a reduction in routes in 62.5 % of the cases, obtaining savings of up to 28.61 % of kilometers traveled daily by the reclaimers. It was also identified that factors such as topography and climate have a direct impact on collection activities.
Keywords: L81; C61; Q53; 330; Logistics; optimization; recovery; solid waste